LC–MS/MS method for the simultaneous quantification of intestinal CYP and UGT activity - Busch, Diana; Fritz, Anja; Partecke, Lars Ivo; Heidecke, Claus-Dieter; Oswald, Stefan (Journal of pharmaceutical and biomedical analysis, 2018)
•Development of an analytical method for the simultaneous quantification ofprobe substrates for human intestinal enzymes•Simultaneous quantification of CYP and UGT metabolites (so far almost exclusively CYP substrates).•Comprehensive method validation according to current bioanalytical guidelines.•Similar/superior sensitivity compared to previously published methods.•Application of the method to characterize the metabolic activity of intestinalCYP2C9 / 2C19 / 2D6 / CYP3A and UGT1A1 / 2B7 Many orally administered drugs are subject to first-pass metabolism by cytochrome P450 (CYP) enzymes and uridine 5′-diphospho-glucuronosyltransferases (UGT). While their hepatic activity is well characterized, respective information about the intestine are very scare due to limited availability of tissue, very low microsomal protein content and the heterogeneity of the individual segments. As a consequence, determination of enzyme kinetic parameters is challenging. It was therefore the aim of this study to develop a sensitive liquid chromatography tandem mass spectrometry method for the simultaneous quantification of CYP and UGT metabolites formed by clinically relevant intestinal biotransformation enzymes: 4-hydroxydiclofenac (CYP2C9), 5-hydroxyomeprazole (CYP2C19), dextrorphan (CYP2D6), 1-hydroxymidazolam (CYP3A), ezetimibe glucuronide (UGT1A) and naloxone glucuronide (UGT2B7). After precipitation of microsomal protein with acetonitrile, analytes were chromatographically separated on a C18 column with gradient elution using acetonitrile and water, both containing 0.1% formic acid and detected with a tandem mass spectrometer operating in positive mode with electron spray ionization. The assay was validated according to current bioanalytical guidelines regarding linearity, accuracy, precision, stability, recovery and matrix effects spanning an analytical range from 1 to 200 nmol/L for each analyte. The developed method was successfully applied to a proof of concept experiment using pooled human jejunal microsomes (50 μg protein/mL) in order to determine enzyme kinetic parameters. Formation of all monitored metabolites followed Michaelis-Menten kinetics and allowed calculation of KM and Vmax values. The developed method may be useful for characterization of enzymatic activity in the human intestine which may allow more precise insights into the intestinal contribution to first pass metabolism of drugs.